PENGARUH PEMBERIAN EKSTRAK BIJI PEPAYA (CARICA PAPAYA LINN) TERHADAP KADAR TRIGLISERIDA PADA TIKUS PUTIH JANTAN GALUR WISTAR (RATTUS NORVEGICUS) YANG DI INDUKSI DIET TINGGI LEMAK - KHAIRATUN NISA; ILHAM HARIAJI (LP2MTBM MAKARIOZ, 2021)
Cardiovascular disease is the leading cause of death worldwide. Based on data from the World Health Organization (WHO)in 2008, an estimated 17.3 million deaths were caused by cardiovascular disease. Based on data from Basic HealthResearch (Riskesdas) in 2018, the incidence of heart and blood vessel disease has increased from year to year. At least 15out of 1000 people or about 2,784,064 individuals in Indonesia suffer from heart disease. To overcome the high incidence ofcardiovascular disease, an effective step is to reduce the risk factors. Modern diets now contain lots of cholesterol. Thisstudy used male Wistar rats (Rattus novergicus) induced by a high-fat diet. Where divided into 4 groups, divided intonegative control, positive control, first treatment (400mg / kgBW) and second treatment (800mg/ kgBW). Takes before andafter a diet and a high-fat diet are taken. Then the data will be processed using the normality test and then the t-test will betested to find the significance of the research results. In this study, the results obtained with the t-test p <0.05, which meansthat there is a relationship between the provision of papaya seed extract and increased Trigliserida levels. In the results ofresearch where the dose of 400mg / kgBW can reduce Trigliserida cholesterol levels in the blood. Where the papaya seedextract has an effect in reducing Trigliserida levels of white wistar rats.